Analysis on the Age Distribution of Sternum Fractures - Schmitt, Sonja; Krinner, Sebastian; Langenbach, Andreas; Hennig, Friedrich F.; Schulz-Drost, Stefan (The Thoracic and Cardiovascular Surgeon, 2018)
Background Sternum fractures (SFs) are described as a rare entity of bony fractures. Various accident mechanisms may cause SF such as the direct impact of traffic accidents and also by indirect mechanisms within the framework of falls. Osteoporotic fractures also play an increasing role in SF, but no reliable data on the age distribution of SF in a representative collective have been published so far.Material and Methods The age distribution of all inpatients treated with SF (S22.2) in Germany from 2005 to 2012 using diagnosis-related group-based routine data was evaluated. Various accident statistics are included in the interpretation of age peaks.Results A total of 47,893 patients (24,960 as main diagnosis and 22,933 as secondary diagnosis) were included in the study. SF is a rarity in childhood, with a share of 1.83% before the age of 16 years, followed by a sudden increase in the frequency up to the age of 20 years. A decrease in the frequency is observed up to the age of 35 years before it increases again to the age of 75 years. Three age peaks can be observed at 18, 55, and 75 years. Those who are older than 65 years account for 43.3% of total SF.Discussion and Conclusion The first age summit after the age of 16 years shows an identical course to the frequency of traffic accidents of this age group, as well as the decline to the fourth decade and the subsequent resurgence up to the fifth decade. After 65 years, the incidence of accidents increases, in particular, the risk of falling in elderly people. In the context of a weaker bone structure, low falls are a common course for fragility fractures. The present analysis of routines shows for the first time the age distribution of the SF taking into account all hospital cases of the observation period.
Keywords: sternum fracture; sternal fracture; age distribution; routine data; medical care